Selected Decisions from the Federal Supreme Court Cassation Bench: Membership to Cooperative Societies for Housing and the Consequence of Change of Residence on Membership Status. - Chane, Gizachew Silesh (Bahir Dar University Journal of Law, 2022)
This case pertains to dispute reagrading membership to Cooperative Societies for Housing and the consequence of change of residence on membership status. The applican was a member of Maranata Housing Cooperative Society in Shewa Robit town, North Shewa Zone, Amhara Region, Ethiopia. She later moved to Addis Ababa following her spouse who moved to Addis Ababa as a member of federal police force. Maranata Housing Cooperative Society dismissed the applicant from membership alleging change of residence. The first instance court ruled in favor of the applican but the subsequent courts of Amhara Region that entatined the case by way of appleal confirmed the dismissal. The Applican took the case to the Federal cassation Bench that reversed ruling of the higher courts and confirmed the decision of the first instance court. The cassation Bench reasoned that though the memerandum of association provided for dismisal from membership due to relocation, such a ground is not stated in the applicable law. As such, memerandum of associations that narrows down the rights of members are contrary to law and cannot be sustained in the eyes of the law.